Book review: Transforming military power since the Cold War: Britain, France, and the United States, 1991–2012 - Piffer, Marcus Vinícius Pinheiro Dutra (2015)
The work deals with the processes of change adopted by the armies of the United States, Britain and France after the Cold War. The authors relate the prevailing situation with the political and strategic imperatives of each of these countries and how these requirements have become the processes of change in military power.Each country was treated in a separate chapter, dealing with the future vision of their army, processes and projects displayed for this transformation and the reasons for success or failure of initiatives.When complete, the authors emphasize the importance of cultural aspects and how these aspects have shaped or limited the processes of change, so that processes with similar goals had very different results. We highlight the fact that the Brazilian Army through a conceptually similar transformation process, increasing the relevance of the work reviewed.